2015
DOI: 10.1097/pas.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the Thymus, Enteric Type

Abstract: We report 2 cases of primary thymic adenocarcinoma with enteric differentiation. One carcinoma occurred in a 41-year-old man as a 7-cm-diameter cystic tumor and the other one in a 39-year-old woman as a 6-cm-diameter solid mass. Both tumors were located in the anterior mediastinum. Clinical staging did not reveal any extrathymic tumor. Histologically, the tumors were classified as adenocarcinoma, not otherwise specified, and a mucinous (colloid) carcinoma, respectively. Immunohistochemically, both tumors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…There have been 46 reported cases of thymic adenocarcinoma [1,6] in addition to our own. Of the 47 cases, 12 (25.5 %) were primary thymic adenocarcinoma with a CDX2-positive phenotype.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…There have been 46 reported cases of thymic adenocarcinoma [1,6] in addition to our own. Of the 47 cases, 12 (25.5 %) were primary thymic adenocarcinoma with a CDX2-positive phenotype.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, Moser et al [1] reported a subtype of thymic adenocarcinoma with CDX2-positive enteric features. CDX2, a homeodomain transcription factor required for the development and maintenance of the intestinal epithelium, is overexpressed by human colon adenocarcinoma [2].…”
Section: Introductionmentioning
confidence: 98%
“…Moser et al . [ 12 ] recently reported two cases of primary thymic adenocarcinoma with CK20 and CDX2 expression, which reflects enteric differentiation, and suggested this is a novel subtype along with 11 reported thymic adenocarcinomas with enteric immunophenotype.…”
Section: Discussionmentioning
confidence: 94%
“…According to a series of case reports in which descriptive classifications are commonly used, thymic adenocarcinomas comprise papillary [ 4 - 6 ], mucinous [ 3 , 7 - 9 ], glandular (or tubular) [ 10 - 12 ], and papillotubular [ 2 , 13 , 14 ] adenocarcinomas. In 2003, Maghbool et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five cases have been reported in the literature since the first case in 1989 [1–5]. They have shown papillary, papillotubular, tubular, or mucinous histological features that were different from the other subtypes of thymic carcinoma.…”
Section: Introductionmentioning
confidence: 99%